The Toxicity Effects of Metformin and the Bioremediation of Metformin in Aquatic Plant Duckweed - Bing Han; Yumeng Jiang; Wenqiao Wang; Yuhan Guo; Yunwen Yang; Yuman He; Qiqi Di; Ziyang Qu; Yun Xing; Lin Yang (Plants)
The release of metformin into the environment poses significant challenges, yet its effects on higher plants remain largely unexplored. In this study, we investigated the impact of metformin exposure on duckweed (Lemna turionifera 5511) across varying concentrations ranging from 0 to 0.16 mg/mL. Our findings revealed that leaves exhibited chlorosis, accompanied by a reduction in biomass, particularly evident at concentrations of 0.1, 0.13, and 0.16 mg/mL of metformin. Chlorophyll fluorescence analysis showed that MF exposure reduced photosynthetic performance, indicated by decreased Fv/Fm and Y (II), and increased Y (ND) and NPQ, suggesting impaired photosystem efficiency and altered energy dissipation. Additionally, genes involved in photosynthesis exhibited significantly reduced transcript abundance. Moreover, metformin was found to alter the transcript levels of GH3 and SAUR genes, which are associated with auxin signaling, and increase the expression of SnRK2, a key component of the abscisic acid signaling pathway. These findings shed light on the toxicological effects of metformin on higher plants, providing valuable evidence regarding the toxicity of this pharmaceutical contaminant. Subsequently, we investigated the absorption of metformin by duckweed (0.128 mg/g FW in 7 days) at a concentration of 0.13 mg/mL, observing a gradual decrease in metformin concentration to zero over a period of 10 days. Notably, the optimal adsorption time was determined to be ten days. Hence, duckweed emerges as a promising candidate for the concurrent bioremediation of metformin-contaminated water and the production of high-quality biomass.